Effects of MDMA on neuroplasticity, amyloid burden and phospho-tau expression in APPswe/PS1dE9 mice. (September 2019) - Abad, Sonia; Ramon-Duaso, Carla; López-Arnau, Raúl; Folch, Jaume; Pubill, David; Camarasa, Jordi; Camins, Antoni; Escubedo, Elena
Background: 3, 4-Methylenedioxymethamphetamine (MDMA) is still one of the most consumed drugs by adolescents. Its abuse is related with cognitive impairment, which seems due to maladaptive plasticity and neural stress. In turn, new hypotheses suggest that Alzheimer's disease (AD) may be promoted by neural stressors. Aims and methods: To test if there is an increase in vulnerability to AD after chronic MDMA consumption, we investigated the effects of this drug on recognition memory and its neurotoxic and neuroplastic effects in a transgenic mouse model of presymptomatic familiar AD (APP/PS1 dE9, Tg). Results: MDMA-treated animals showed recognition memory deficits, regardless of genotype, which were accompanied by changes in plasticity markers. Tg mice showed an impaired expression of Arc compared with wild-type animals, but exposure to MDMA induced an increase in the expression of this factor of the same percentage in both genotypes. However, the expression of c-fos, BDNF and p-CREB was not significantly altered by MDMA treatment in Tg mice. Although Tg mice had higher free choline levels than wild-type mice (about 123%), MDMA did not modify these levels in any case, ruling out any specific effect of this drug on the acetylcholine pathway. MDMA treatment significantly increased the presence of cortical amyloid plaques, as well as Aβ40, Aβ42 and secreted APPβ levels in Tg mice. These plaques were accompanied by increased tau phosphorylation (S199), which does not seem to occur via the canonic pathway involving AKT, CDK5 or GSK3β. Conclusions: The present results support previous evidences that MDMA can contribute to the amyloid cascade.